FRI0045 Oral microbiome profile in rheumatoid arthritis patients: association between tongue biofilm porphyromonas gingivalis amount and disease activity. (15th June 2017) - Ceccarelli, F; Orrù, G; Pilloni, A; Bartosiewicz, I; Perricone, C; Martino, E; Lucchetti, R; Fais, S; Vomero, M; Olivieri, M; Franco, M Di; Priori, R; et al.
Abstract : Background: P. gingivalis is a Gram-negative anaerobic bacterium usually located in the oral cavity, as component of microbiome. Next to the established association with oral cavity diseases, such as periodontitis and halitosis, in the last years a growing interest has been addressed to its implication in the development of autoimmune diseases, such as Rheumatoid Arthritis (RA). The ability of P. gingivalis to citrullinate peptides is the most relevant link with RA. Indeed, this bacterium has several virulence factors directly contributing to its chronic inflammation regardless of citrullination. Data from the literature demonstrated the ability of P. gingivalis in inducing the production of several inflammatory cytokines, such as TNF, IL6 and IL17, through the TLR signaling pathways. Objectives: In the present case-control study, we aimed at analysing tongue microbiome in a large RA cohort, focusing on the evaluation of P. gingivalis presence and quantification. Methods: We enrolled 143 RA patients (1987 ACR criteria; M/F 32/111, mean±SD age 57.5±19.8 years, mean±SD disease duration 155.9±114.7 months); 36 periodontitis (M/F 11/25, mean±SD age 56±9.9 years, mean±SD disease duration 25.5±20.9 months); 57 (M/F 12/45, mean ±SD age 61.4±10.9 years, mean ±SD disease duration 62.3±66.9 months) affected by knee osteoarthritis or fibromyalgia (control subjects – CS). All subjects underwent a clinical evaluation in order to assess disease activity by DAS28. Blood serum samples were obtained to evaluate the presence of ACPA by a commercial ELISA kit. Finally, a standard cytologic swab to collect tongue biofilm samples was performed and the presence of P. gingivalis was evaluated by PCR method. Results: The prevalence of P. gingivalis resulted significantly higher in RA and PD patients in comparison with CS (P=0.01 and P=0.003, respectively). No correlation between bacterium presence and ACPA was found. When evaluating the percentage of P. gingivalis on the total tongue biofilm, we observed a significant correlation between this measure and DAS28 values (r=0.4, P=0.01). Furthermore, RA patients in DAS28 remission showed a significantly lower prevalence of P. gingivalis in comparison with non-remission patients (P=0.02). Conclusions: In the present study, for the first time we assessed the prevalence of P. gingivalis, i.e. its percentage on the total tongue biofilm, in a large RA cohort. A significant correlation between the amount of P. gingivalis on total tongue biofilm and disease activity was observed. There was no association with ACPA, suggesting that this bacterium, beyond citrullination, could be implicated in triggering a pro-inflammatory state in RA. Disclosure of Interest: None declared